2019
DOI: 10.3390/s19214731
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Sensitivity in Stimulated Brillouin Scattering of 1060 nm Single-Mode Fibers

Abstract: With the rapid advancement of Yb-doped fiber lasers (YDFL) whose output wavelength is near 1060 nm, passive fibers to carry the high optical power at the spectral range are also gaining significant importance. Stimulated Brillouin scattering (SBS) in the passive fibers connecting components in the lasers, especially, can set a fundamental limit in the power handling of YDFL systems. We experimentally analyzed SBS characteristics of passive single mode fibers (SMF) at a wavelength of 1060 nm. For two types of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Other optical methods for continuous thermal sensing are being explored; for example, the use of Raman scattering [55] and Brillouin scattering [56][57][58] seems promising. Optical techniques would typically suffer from insufficient thermal sensitivity at lower temperatures, due to reduction of the coefficient of thermal contraction for nearly all materials when approaching absolute zero, and, practically, at temperatures below 15-20 K. While most of the optical quench detection experiments were conducted at 77 K, it is technically possible to extend the sensitivity range down to lower temperatures using specially designed optical fibers.…”
Section: Optical Techniquesmentioning
confidence: 99%
“…Other optical methods for continuous thermal sensing are being explored; for example, the use of Raman scattering [55] and Brillouin scattering [56][57][58] seems promising. Optical techniques would typically suffer from insufficient thermal sensitivity at lower temperatures, due to reduction of the coefficient of thermal contraction for nearly all materials when approaching absolute zero, and, practically, at temperatures below 15-20 K. While most of the optical quench detection experiments were conducted at 77 K, it is technically possible to extend the sensitivity range down to lower temperatures using specially designed optical fibers.…”
Section: Optical Techniquesmentioning
confidence: 99%
“…This ring fiber laser employs the element described for Figure 1c. In 2019, the importance of the cross-section's passive fiber used in SBS fiber laser sensors was demonstrated by Sanggwon Song et al [105]; the authors demonstrated a sensitivity variation of 0.11 MHz/ • C using SMF fibers for 1060 nm-with different cross sections. The maximal sensitivity achieved was 1.83 MHz/ • C (see Figure 7c).…”
Section: Temperature Fiber Laser Sensorsmentioning
confidence: 99%
“…et al [14] analyzed the SBS slow light by filling liquid into a PCF core in 2016. Sanggwon Song et al [15] reported systematic experimental characterizations of the SBS in passive 1060 nm SMFs using a highly sensitive optical heterodyne method with a narrow linewidth CW (continuous wave) laser operating at a wavelength of 1064 nm. It can be seen from this literature that the research on SBS temperature sensing is mainly based on refractive index of PCF, because the transmission characteristics of light changes with the various refractive indexes of the filled liquid induced by varying temperature, and the previous research focused on SBS slow light.…”
Section: Introductionmentioning
confidence: 99%